Institutions and economic growth: the case of Zambia - Zulu, Jack Jones (My University, 2016)
Zambia has had impressive economic performance in the last decade and half, however its growth remains unsustainable due to a number of factors that range from poor terms of trade to challenges in macroeconomic management. In addition, the country’s weak economic and political institutional framework characterised by insecure property rights and uncertainty in the policy environment pose further challenges to economic growth. Although the country has undertaken a number of economic reforms in recent years to spur growth, their impact has been modest because of weak institutional setups and capacity constraints. Notably, certain key policy reforms and programmes that are critical for enhancing economic performance in Zambia have not been implemented because of institutional and administrative weaknesses underpinned by policy inconsistencies and policy reversals. Against this background, the main purpose of this study is to investigate the impacts of formal institutions particularly property rights and political instability on economic growth in Zambia. It achieves this by extending Fedderke et al. (2011)’s time series on property rights and political instability measures on Zambia by constructing comparable indices that are later merged with the initial series. The merged series are then used to capture the institutional dimensions on economic output in Zambia from 1965 to 2010. The study uses in its methodology a PSS-F test to determine causality among variables of interest and later applies the VECM estimation procedure to determine cointegration and long-run relationships among the regressors. Despite the increasing role and influence of formal institutions in economic development, there have been relatively few empirical studies that have specifically examined their impacts at country level. This study is therefore an attempt to partially fill the void by throwing light on the impact of property rights and political instability on Zambia’s economic growth over the study period. The study findings have confirmed the hypothesis that there is a strong and positive relationship between property rights and the level of economic growth. The results have been validated using Zambia as a case study and hence the findings are consistent with empirical evidence and economic theory in new institutional economics (NIE). Noteworthy is the strong and positive effect of property rights on real GDP—clearly suggesting that potential investors will always take into account a country’s institutional environment before investing their resources. This means that a good performance in the rating of the property rights index on the scale between 0 and 100 leads to a corresponding strong economic performance in Zambia. By implication, a higher rating of the property rights index suggests a well secured regime of property rights. Conversely, a lower rating of the property rights index implies deterioration in the quality and enforcement of property rights in the country and hence adverse to economic growth. Thus, the findings are in line with several similar empirical works that conclude that formal economic institutions (property rights) are the fundamental cause of income differences and longrun growth between and among countries. As expected, our study also found a strong but negative relationship between political instability and economic performance. This means that perverse political institutions such as violent civil protests, political violence, attempted military coups, labour and/or industrial unrest in Zambia are a disincentive to economic growth as they discourage long-term investments. Investors are generally driven by perceptions, that is, the more politically stable an economy is assumed to be, the higher the chances of attracting foreign direct investments. Conversely, the stronger the negative perceptions about an economy the less likely will investors bring in their resources—hence the need for political stability. The findings are consistent and comparable to many other studies that found that political instability was significantly related to economic growth and that an increase in instability, other things being equal, always tends to lower real growth rate over time. The study also examined the impacts of selected macroeconomic policy variables namely foreign direct investments (FDI), credit to the private sector (CRDTP), trade openness (TROP), capital formation (CALARAT) and human capital (ENROLL) on Zambia’s real GDP and found that they had a strong feedback effect on growth performance. In terms of policy implications, the study recommends that authorities should invest in efforts that strengthen the regime of property rights and the rule of law for strong economic performance in Zambia. More specifically, the authorities should respect and enforce private property rights through impartial courts of law to instil confidence in the investor community. In addition, the government should promote social dialogue and foster an environment of industrial harmony to avoid labour-related unrest and political conflicts (political instability) that have a potential to hurt the business environment by scaring off would-be investors.
Thesis Presented for the Degree of Doctor of Philosophy In the Faculty of Law, Commerce and Management University of Witwatersrand June 2016
Keywords: Zambia--Economic conditions; Zambia--Economic policy; Right of property--Zambia; Institutional economics